2017
DOI: 10.5603/mrj.2017.0001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic chiral inversion of 2-arylpropionic acid derivatives (profens)

Abstract: 2-arylpropionic acid derivatives (profens) are one of the most popular anti-inflammatory, analgesic, and antipyretic drugs. They belong to a group of nonsteroidal anti-inflammatory drugs (NSAID) and exhibit metabolic chiral inversion. Enantiomers of these chiral drugs are often characterised by different pharmacological activity. It is estimated that the values of metabolic chiral inversion of (R)-ibuprofen in humans are between 35 and 70%, depending on the condition of the liver and the intake of other medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
1
6
0
5
Order By: Relevance
“…The IC50 values for Aβ42 inhibition estimated for R-flurbiprofen was 800.4 ng/ml that is equivalent to 3276.89 nM and was consistent with what previously reported by other authors using identical human neuroglioma cell line [12]. R-flurbiprofen was chosen as a reference drug because it reduces Aβ42 levels by targeting γ-secretase without any side effects related to inhibition of cyclooxygenase (COX) as it lacks COX activity, and in humans, undergoes very limited chiral inversion to the S-enantiomer that is active against COX [24] as well as, it was suggested that the high dose regimen may significantly slow the cognitive and functional decay of mild affected patients [25]. In our study, inhibition of Aβ42 was recognized in our red calyces for both water and aqueous ethanol extracts with concentrations less than the reference drug by approximately one and half to three times.…”
Section: Fig 2 Dose Response Activities Of Dark Red Roselle At Aqueous Extraction Against Formation Of Aβ42 Peptidesupporting
confidence: 85%
“…The IC50 values for Aβ42 inhibition estimated for R-flurbiprofen was 800.4 ng/ml that is equivalent to 3276.89 nM and was consistent with what previously reported by other authors using identical human neuroglioma cell line [12]. R-flurbiprofen was chosen as a reference drug because it reduces Aβ42 levels by targeting γ-secretase without any side effects related to inhibition of cyclooxygenase (COX) as it lacks COX activity, and in humans, undergoes very limited chiral inversion to the S-enantiomer that is active against COX [24] as well as, it was suggested that the high dose regimen may significantly slow the cognitive and functional decay of mild affected patients [25]. In our study, inhibition of Aβ42 was recognized in our red calyces for both water and aqueous ethanol extracts with concentrations less than the reference drug by approximately one and half to three times.…”
Section: Fig 2 Dose Response Activities Of Dark Red Roselle At Aqueous Extraction Against Formation Of Aβ42 Peptidesupporting
confidence: 85%
“…O objetivo estrutural da enzima e o formato e distribuição de carga no sítio receptor possibilitou o planejamento do composto protótipo. Seguidamente utilizando a técnica da simplificação molecular o sistema cis-perisoquinolínico foi trocado por um anel piperazínico, subtraindo dois centros estereogênicos, originando o medicamento indinavir representado na figura 3 (13) . Consequentemente, por meio da simplificação molecular ficou evidenciado a importância desse método para a modelagem molecular, possibilitando o planejamento estrutural do medicamento indinavir, adquirido racionalmente da protease viral do HIV.…”
Section: ____________________________________________________________...unclassified
“…Consequentemente, por meio da simplificação molecular ficou evidenciado a importância desse método para a modelagem molecular, possibilitando o planejamento estrutural do medicamento indinavir, adquirido racionalmente da protease viral do HIV. Desta maneira, a avaliação da capacidade de pequenas moléculas interagirem com enzimas alvo pré-selecionadas estabelece a importância da modelagem molecular do fármaco em questão (13) .…”
Section: ____________________________________________________________...unclassified
“…Nonsteroidal anti-inflammatory drugs (NSAIDs) play an important role in modern therapy. Since most NSAIDs are chiral and each enantiomer shows different biological and therapeutic activities, the enantioselective separation of this main drug family is important [3][4][5].…”
Section: Introductionmentioning
confidence: 99%